Outcomes of scapulothoracic fusion in facioscapulohumeral muscular dystrophy: A systematic review. (April 2020) - Kord, Dorsa; Liu, Eva; Horner, Nolan S; Athwal, George S; Khan, Moin; Alolabi, Bashar
Background: Facioscapulohumeral muscular dystrophy (FSHD) is a rare condition associated with selective weakness of the muscles of the upper arm, face, and shoulder girdle, negatively affecting daily activities. Scapulothoracic arthrodesis may restore shoulder function and improve quality of life. The purpose of this review is to evaluate the outcomes and complications of scapulothoracic arthrodesis in FSHD patients. Methods: Medline, Pubmed, and Embase were systematically searched. Studies were included if they described scapulothoracic arthrodesis in FSHD with follow-up, and outcomes were adequately reported. Thirteen eligible articles reported the outcomes of 199 arthrodesis in 130 patients. Results: The mean gain of shoulder forward elevation and abduction were 45° (p < 0.05) and 40° (p < 0.05), respectively. There was an overall cosmetic satisfaction and improved performance of daily activities. There is limited and heterogeneous data on changes in pulmonary function, but such changes are clinically insignificant. The rate of complications was 41% of which 10% were serious, requiring an intervention or re-admission. The most common complications were hardware failure (8%), non-union (6%), and pneumothorax (5%). Discussion: Scapulothoracic arthrodesis improved cosmesis, performance of daily activities and shoulder motion with no clinically significant loss of pulmonary function. The complication rate is high, and some are potentially serious.